Fibronectin mediates mesendodermal cell fate decisions - Cheng, Paul; Andersen, Peter; Hassel, David; Kaynak, Bogac L.; Limphong, Pattraranee; Jürgensen, Lonny; Kwon, Chulan; Srivastava, Deepak (Development, 2013)
Non-cell-autonomous signals often play crucial roles in cell fate decisions during animal development. Reciprocal signaling between endoderm and mesoderm is vital for embryonic development, yet the key signals and mechanisms remain unclear. Here, we show that endodermal cells efficiently promote the emergence of mesodermal cells in the neighboring population through signals containing an essential short-range component. The endoderm-mesoderm interaction promoted precardiac mesoderm formation in mouse embryonic stem cells and involved endodermal production of fibronectin. In vivo, fibronectin deficiency resulted in a dramatic reduction of mesoderm accompanied by endodermal expansion in zebrafish embryos. This event was mediated by regulation of Wnt signaling in mesodermal cells through activation of integrin-β1. Our findings highlight the importance of the extracellular matrix in mediating short-range signals and reveal a novel function of endoderm, involving fibronectin and its downstream signaling cascades, in promoting the emergence of mesoderm.
Gesehen am 12.04.2021